An empirical investigation of real farm incomes across Indian states between 1987-88 and 2011-12 - Deepankar Basu; Kartik Misra (University of Massachusetts, Department of Economics, 2022)
Using unit-level data from various rounds of the Employment and Unemployment Survey of the National Sample Survey Organisation, we present the first consistent time series of average real farm income per cultivator for 18 major Indian states for 1987-88, 1993-94, 1999-00, 2004-05, 2007-08, 2009-10, and 2011-12. Using this data, we study two sets of issues. First, how did real farm income evolve across these 18 Indian states? Which states have high levels and growth rates of real farm incomes? Is there any evidence for convergence of real farm incomes across Indian states? We find evidence for unconditional convergence, which suggests that states with relatively lower farm incomes have, on average, grown at relatively faster rates. But the tendency towards convergence has not been strong enough to change relative rankings of states (by real farm income per cultivator) in any significant way. Second, did the market-oriented reforms of agricultural marketing systems increase real farm incomes? We find that market-oriented reforms did not increase real farm incomes.
Keywords: O13; Q1; 330; agricultural income; Indian states; conditional convergence; market-oriented reforms